(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Alzheimer’s disease (AD) represents the most prevalent neurodegenerative disorder worldwide, characterized by progressive neuronal loss, synaptic failure, and the pathological accumulation of amyloid-β (Aβ) plaques and neurofibrillary tangles. For decades, the therapeutic landscape has been dominated by neuroprotection—strategies aimed at shielding existing neurons from further damage. However, the sobering reality of clinical trials reveals a critical limitation: neuroprotection alone cannot reverse the neuronal devastation already wrought by the disease. As of 2026, over 200 drug candidates have failed in Phase III trials, with most approaches focusing on amyloid clearance or anti-inflammatory modulation without addressing the fundamental deficit of neuronal replacement.